The enhancement of polymer composite coating by using a waste glass powder as alternative reinforcement - Phummiphat Buaphuen; Worawut Makcharoen; Wanwilai Vittayakorn (Ferroelectrics, 2022)
Epoxy-based composites are widely used as a surface coating in the aircraft, automobile and microelectronic industries due to theirs great mechanical properties, excellent strength-to-weight ratio, lightweight, and good machinability. However, the epoxy-based coating has poor corrosion resistance in a severe environment such as in seawater. The incorporation of various fillers into epoxy resins can yield high-performance composites having high strength, lightweight, multifunctional properties and also improve corrosion resistance. Therefore, this study focuses on the preparation of inorganic nanoparticles filled in an epoxy resin matrix to create high-performance composites. The waste glass powder (WGP) was selected to use as the alternative reinforcement in epoxy resin-based composites in order to search for a sustainable and recycling filler along with the use of commercial SiO2 as a comparative filler. The broken glass from household waste was processed through a high-speed vibratory milling technique until reaching the micrometer level. The physical properties, microstructure, mechanical properties, electrical properties, water absorption and corrosion resistance of all composites are investigated. The results show that after mixing WGP with an epoxy resin matrix, both Vickers hardness and abrasion resistance significantly increase compared to the neat epoxy resin whereas the water absorption ability of composites decreases. For the electrical properties, WGP does not show a significant effect on dielectric constant, dielectric loss and resistivity whereas the anticorrosive performances of the WGP/epoxy resin composite coating are improved.
Keywords: Tribology and Wear Analysis; Natural Fiber Reinforced Composites; Polymer Nanocomposites and Properties